Oral glucose tolerance assay of extract from Mangifera foetida l. and Pandanus amaryllifolius roxb. leaves - RETNANINGTYAS, YUNI; CRISTIANTY, FRANSISKA MARIA; KRISTININGRUM, NIA; WARDANI, PRAMUDIA (Universitas Syiah Kuala, 2024)
This study examines the potential antidiabetic activity of a combination of Mangifera foetida L. and Pandanus amaryllifolius Roxb. leaves. Mangifera leaves contain a compound called mangiferin, which acts as an antidiabetic and antioxidant. On the other hand, Pandanus leaves, are rich in terpenoids and steroids that also possess anti-diabetic effects. An Oral Glucose Tolerance Test (OGTT) was conducted on male mice of the Babl/c strain to assess the antidiabetic effects. The test involved administering a combination of ethanolic leaf extracts from Mangifera foetida L. and Pandanus amaryllifolius Roxb. in a 1:1 ratio. The study followed a pre-test design with a control group, comprising six treatment groups, each consisting of four male mice. The groups were described as follows: Group 1 was served as the normal group without any treatment. Groups II-IV received single extracts or combinations of extracts at doses of 62.5 mg/200g BW, 125 mg/200g BW, and 250 mg/200g BW. Group V acted as the positive control and was given oral glucose and glibenclamide at a dose of 0.09 mg/200g BW. Group VI was served as the negative control, receiving oral glucose and distilled water. The group that exhibited the highest percentage of decreased blood sugar levels was the one given oral glucose at a dose of 0.078g/20g BW of mice, along with the combination of Mangifera foetida L. and Pandanus amaryllifolius Roxb. leaves extract (1:1) at a dose of 35 mg/20g BW. This group demonstrated a decrease of 71.985 4.858 in blood glucose levels. The ANOVA analysis confirmed that the percentage decrease in blood sugar levels was significantly different from the positive control, indicating a higher effectiveness of the combination treatment in reducing blood glucose levels than the positive control.